U.S. Dental School Deans' Attitudes About Mid–Level Providers. Issue 11 (1st November 2013) - Aksu, Mert N.; Phillips, Elizabeth; Shaefer, H. Luke
Abstract : The introduction of mid–level providers to the U.S. dental workforce is currently a topic of heated debate. As little is known about the opinions of those who educate oral health professionals on the subject of such practitioners, a survey of U.S. dental school deans was undertaken to gauge their attitudes about alternative workforce models in the dental profession. The survey was sent to deans of the then–fifty–eight U.S. schools of dentistry; forty–four responded for a 76 percent response rate. Over three–fourths of the respondents agreed that the scope of practice for both dental hygienists and dental assistants should be expanded; significantly, over half agreed that the future of dentistry should include a dental therapist–type practitioner. Moreover, three–fourths agreed that such practitioners or expanded–duty hygienists would improve access to care for the underserved, and between half and two–thirds agreed that the quality of care delivered by these professionals would not be a problem. The attitudes of the deans about mid–level providers falls somewhere between that reported for U.S. dentists generally, who tend to be skeptical, and for dentists in other countries, who, once they have worked in a system with dental therapists, tend to be supportive.